Implementasi Program Adiwiyata untuk Menumbuhkan Kepedulian Lingkungan Siswa: Studi Kasus di SD Negeri Ledug - Anisa Anggun Kinasih; Badarudin Badarudin (Universitas Muhammadiyah Mataram, 2026)
Abstract: This study aims to analyze the implementation of the Adiwiyata Program at Ledug Public Elementary School, the forms of students' environmental awareness, as well as supporting and inhibiting factors. The study population was the entire school community, with a sample of 5 informants (principal, class teacher, Adiwiyata teacher, DUJO students, and parents) selected purposively. Data were collected through observation, interviews, and documentation. The results of the study indicate that the program implementation runs through four main pillars and has succeeded in developing students' environmental awareness as reflected in increased understanding, attitudes, motivation, and environmentally friendly behavior. Supporting factors include the principal's leadership, parental participation, and mutual cooperation, while inhibiting factors are budget limitations, minimal teacher training, and misalignment of school and home values. The implications of the study indicate a significant influence of parental leadership and participation on the program's success. These results can be an alternative for Adiwiyata-based elementary schools in strengthening participatory aspects, improving administration, and strengthening communication with parents.Abstrak: Penelitian ini bertujuan menganalisis implementasi Program Adiwiyata di SD Negeri Ledug, bentuk kepedulian lingkungan siswa, serta faktor pendukung dan penghambatnya. Populasi penelitian adalah seluruh warga sekolah, dengan sampel 5 informan (kepala sekolah, guru kelas, guru pengampu Adiwiyata, siswa DUJO, dan orang tua) yang dipilih secara purposive. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan implementasi program berjalan melalui empat pilar utama dan berhasil mengembangkan kepedulian lingkungan siswa yang tercermin dalam peningkatan pemahaman, sikap, motivasi, dan perilaku ramah lingkungan. Faktor pendukung meliputi kepemimpinan kepala sekolah, partisipasi orang tua, dan gotong royong, sedangkan penghambatnya adalah keterbatasan anggaran, minimnya pelatihan guru, dan ketidakselarasan nilai sekolah dengan rumah. Implikasi penelitian menunjukkan pengaruh signifikan kepemimpinan dan partisipasi orang tua terhadap keberhasilan program. Hasil ini dapat menjadi alternatif bagi sekolah dasar berbasis Adiwiyata dalam penguatan aspek partisipatif, perbaikan administrasi, dan penguatan komunikasi dengan orang tua.